CERTIFICATION ACCELERATION POLICY WAQF LAND IN INDONESIA - Dakum Dakum; Nurwati Nurwati; Dwi Putra Yullhaq (Jurnal Cendekia Hukum, 2022)
The policy for accelerating waqf land registration is a policy issued by the government continuously from 2017 to 2020 through the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency of the Republic of Indonesia (ATR/BPN RI) and the Ministry of Religion of the Republic of Indonesia (Kemenag). However, until now the number of waqf lands in Indonesia that have not been certified is still considered high at around 39.63%. Thus, the purpose of this study is to analyze the extent to which the government has issued a policy to accelerate waqf land certification issued by the government in Indonesia. The formulation of the problem in this study is how to analyze government policies as an effort to accelerate the registration of waqf land certification and what are the implications for accelerating waqf land certification in Indonesia? This research method is normative juridical, while the data analysis is qualitative. The results of this study indicate the policy of accelerating waqf land certification in Indonesia is the government's effort in accelerating waqf land certification, namely by issuing the Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency of the Republic of Indonesia (ATR/BPN RI) Number 2 of 2017 concerning Procedures for Land Registration Waqf at the Ministry of ATR/BPN, Regulation of ATR/Head of BPN Number 6 of 2018 concerning Complete Systematic Land Registration (PTSL), and Memorandum of Understanding between the Ministry of Religion (Kemenag) and ATR/BPN of 2020 concerning Acceleration of Waqf Land Certification, all of these regulations provide guidelines that make it easier to manage waqf land certification. In addition, the implication of this regulation is that stakeholders in the process of certifying waqf land should be able to respond properly so that the acceleration of waqf land certification in Indonesia can be realized.